Grief in medicine from the vision and skin of the healthcare professional - Díaz Avila, Erik Gabriel; Fernández-Carrera Muchova, Marcela; Sánchez Villanueva, Teresa; Sánchez Calvo, Vega; Mesonero Robles, Jesús Francisco (Spanish Journal of Medical Education, 2021)
Grief is a natural process that people go through after the loss of a loved one. During the current COVID-19 pandemic, health professionals have been victims, as they have had to face an unprecedented situation in which their own mental health has been put at stake. The main objective of the study has been to analyze the grief in health professionals during the current COVID-19 pandemic. A literatura review, non-systematic was carried out in the different scientific databases to analyze the grief in the field of medicine linked to the grief experienced by health professionals, focused on the current situation of health crisis, as well as the problems added by the COVID-pandemic. 19. The COVID-19 pandemic has highlighted the importance of mourning and a fair farewell, which could not be given in most cases. The preparation that health professionals must receive to face this process and even future health professionals is imperative. The importance of training and mental health care is evident, both in patients, relatives, health personnel and future health professionals. At the same time, resilience focused on aspects related to grief must be guaranteed.